2017
DOI: 10.1037/xhp0000312
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of perceptual and motor experience of an observed action to anticipating its result.

Abstract: To gain deeper insight into respective contributions of perceptual and motor experience of an observed action to anticipating its result, we examined the perceptual anticipation of players with different action roles in striking sports. Baseball pitchers and batters at both advanced and intermediate levels were asked to make a decision about whether to swing the bat when viewing a series of videos showing incomplete sequences of a model pitcher throwing a strike or a ball. The results revealed that first 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 38 publications
5
33
1
Order By: Relevance
“…For example, skilled baseball batters showed higher percentages of appropriate swings than novices when they were asked to respond to a pitch that was interrupted before the ball crossed the home plate (Ranganathan & Carlton, 2007). Similarly, previous work from our laboratory found that even in the case of perceptually judging whether to swing or not (without performing a swinging action) in response to a video showing incomplete pitching sequences and ball trajectories, skilled batters could more sensitively discriminate when to swing at strikes over balls than intermediate batters (Chen, Lee, Lu, Huang, & Yen, 2017). These findings suggest that skilled batters can extract and utilize crucial information from the actions of the pitcher along with the early ball flight trajectory to determine swing decisions, whereas less skilled batters have to wait until they can visualize the entire pitching sequence with longer ball trajectories.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…For example, skilled baseball batters showed higher percentages of appropriate swings than novices when they were asked to respond to a pitch that was interrupted before the ball crossed the home plate (Ranganathan & Carlton, 2007). Similarly, previous work from our laboratory found that even in the case of perceptually judging whether to swing or not (without performing a swinging action) in response to a video showing incomplete pitching sequences and ball trajectories, skilled batters could more sensitively discriminate when to swing at strikes over balls than intermediate batters (Chen, Lee, Lu, Huang, & Yen, 2017). These findings suggest that skilled batters can extract and utilize crucial information from the actions of the pitcher along with the early ball flight trajectory to determine swing decisions, whereas less skilled batters have to wait until they can visualize the entire pitching sequence with longer ball trajectories.…”
Section: Introductionsupporting
confidence: 71%
“…This decision was also possibly made to avoid being called out on strikes, especially because pitches in this study were ambiguous for only incomplete pitching action and pitch trajectory was shown. For uncertain rates, we found that SBs had a lower rate than the other two groups, but the differences were not statistically significant, even using similar pitching videos for experimental stimuli as in our previous study (Chen et al, 2017). This could possibly be because, in this study, batters of three skill levels were compared and only very short videos 4.2 | AON is involved in anticipating one's own response to an observed action At the neural level, we found a clear spatial overlap of activation patterns within the AON among the three groups, replicating previous findings (Abreu et al, 2017;Bishop & Wright, 2018;Karlinsky et al, 2017; for a review, see Smith, 2016).…”
Section: Perceptual Anticipation Ability Increases As a Function Ofcontrasting
confidence: 59%
See 2 more Smart Citations
“…There is only one “mismatched” study to our knowledge that investigated the contribution of visual and motor expertise to anticipation in sport. Chen et al () investigated whether advanced and intermediate baseball batters with visuomotor response expertise and pitchers with motor expertise could anticipate whether to swing or not swing at pitches (an open skill) in a video temporal occlusion paradigm. First, they found that advanced batters were significantly superior to intermediate pitchers and batters at anticipating strikes based upon an early ball flight occlusion.…”
Section: Behavioural Evidence Of Visual and Motor Contributions To Thmentioning
confidence: 99%